Juventude, revitalização cultural e a temática das gerações - Simone Ribeiro Nolasco; Nicanor Palhares Sá (EccoS – Revista Científica)
In this paper we present reflections on the youth categories and generation, studied inside of a doctorate research and we investigated the cultural practice of a political view and identifying order of intensification, organized by secondary school students. It is the production of student’s newspapers between the years of 1926 and 1937, that in order of the public sphere, intra and extra walls of the secondary school, to get in highlights new ways and new spaces of individual and collective actions of youth; Young people that are subject and they reach the ears in movements and actions of cultural character which are composed of a political dimension to create new proposals, stiffen interests, became sociable ideas and power relations. Second Lara (2008), it is a type of social participation badly recognized given its format located, fluid and discontinuous. We search still in this work, raise the challenges to work with the theme of the youth in its connection with the category of generation and in this perspective, expand the possibilities of approach to this subject.